Preparation CuO and CuCO3Cu (OH) 2 Crystal Nano Particles by Using Microemulsion Method - Sabiha Jabbar Beden; Hassan Ismail Dumbous; Kassim Mohammed Sahan (Engineering and Technology Journal, 2012)
A microemulsion method for preparing colloidal copper nanoparticles in microemulsion is reported. The obtained copper carbonate CuCO3⋅Cu(OH)2 nanoparticle and copper oxide CuO nanoparticle were characterized by powder X-ray diffraction (XRD), atomic force microscopy(AFM),transmission electron microscopy (TEM) and Xray fluorescent(XRF) analysis, the purity of material and average particle size about 10 nanometer.. A microemulsion is thermodynamically stable ,optically isotropic derision of two immiscible liquids consisting of nano-size (CuSO4.5H2O) domains of one or both liquids in the other (white oil),stabilized by an interfacial film of the surface-active molecules. The materials mixed to have new immiscible solution , add chemical materials to reduce surface tension and to reduced interfacial atomic bonds to very low level , the very fine dispersed spherical micelles in microemulsion are thermodynamically stable due to a combination of very low interfacial tension very small nanoparticles diameter of (2-5) nm. Addition another of chemical material as react agent or reduced agent and precipitate agent to product final material CuCO3⋅Cu(OH)2.Synthesis of monodispersed CuCO3⋅Cu(OH)2 nanoparticles with refractive index similar to glass plates by using ultrasonic spray pyrolysis technique by method .Yielding homogeneous ,low defect thin films of high transparency ,that can be used as color filters for liquid crystal displays .